The Morphology, Taxonomy, and Phylogenetic Analyses of Five Freshwater Colonial Peritrich Ciliates (Alveolata, Ciliophora), Including the Descriptions of Two New Species - Wu, Tong; Wang, Zhe; Duan, Lili; El-Serehy, Hamed; Al-Farraj, Saleh A.; Warren, Alan; Liu, Yujie; Wang, Chundi; Lu, Borong (Frontiers in Microbiology, 2021)
The morphology and phylogeny of two new sessilid species, Zoothamnium weishanicum n. sp. and Epicarchesium sinense n. sp., two insufficiently known species, Zoothamnium arbuscula Ehrenberg, 1831 and Zoothamnium hentscheli Kahl, 1935, and a well-known species, Carchesium polypinum (Linnaeus, 1767) Ehrenberg, 1838, collected from freshwater habitats of China, were investigated. Zoothamnium weishanicum n. sp. is characterized by its inverted bell-shaped zooids, double-layered peristomial lip, alternately branched stalk and two different-length rows in infundibular polykinety 3 (P3). Epicarchesium sinense n. sp. is recognized by its asymmetric-pyriform zooids, single-layered peristomial lip, conspicuous cortical blisters on the pellicle, dichotomously branched stalk, and P3 containing one short inner row and two long outer rows. Based on previous and newly obtained data of the three known species, improved diagnoses and redescriptions are provided including, for the first time, data on the infraciliature of Z. arbuscula and Z. hentscheli. In addition, we analysed the phylogeny of each species based on SSU rDNA sequence data.